SOME IMPORTANT AYURVEDIC HERBAL DRUGS FOR THE MANAGEMENT OF MENTAL ILLNESS IN CHILDREN (AYUSHDHARA, 2018)
Ayurveda is holistic medical system of science of life and knowledge Vedas. It explains human body is combination of physical structure and mental behavior. Mental illness interchangeably knows as psychological disorder. In this context Ayurveda, mention psychological disorder like Apsmara and Unamada. Other condition like Atattvaabhinivesha, Bhaya, Harsha, Shoka, Udvega and Avasada are included in mental disease. Therefore, ADHD, Dyslexia, Autism and Mental retardation are correlated with sign and symptoms of these conditions. Some symptoms are seen through unbalancing Tridosha, aggravating Doshas and Trigunas (Satva, Raja, Tama). In Ayurvedic pharmacology described about Vacha, Mandukaparni, Bramhi, Shankhapushpi Jatamasi, Jyotismati and Kushmanda are effective in mental illness due to their Medhya, Smritivardhaka, Sangyasthapaka and Rasayana properties. Experimental and clinical researches also mention these drugs are helpful for the treatment of mental illness or psychological disorder. Keeping this fact in view, an effort has been arranged to collect the information related to Ayuevedic Herbal drug from different Samhitas, Nighantu and Ayurvedic pharmacology books and other texts, regarding its therapeutic uses in mental illness and related condition. Present information is key point and facts may help the researchers to develop treatment modality for mental illness in children through Ayurveda.